Yielding of old and modern Polish wheat cultivars under different nitrogen inputs as assessed*by combined using AMMI and cluster analyses. - Paderewski, J.; Mądry, W.; Rozbicki, J. (Plant Breeding and Seed Science, 2010)
The experimental material consisted of 15 winter wheat cultivars (14 Polish-bred cultivars and one British cultivar) representing the results of over 100 years of breeding. The cultivars were tested in two-factor field experiments (cultivars were one factor and nitrogen fertilization rates, the other factor) carried out in split-plot design across two consecutive years. This paper demonstrates a combined using AMMI and cluster analyses for effective and efficient estimate of grain-yield response to investigated environments (combinations of 2 years × 3 nitrogen fertilization rates). First, homogenous groups of cultivars were identified in terms of their genotypic profile of AMMI(s) estimates of GEI effects using Ward’s method of cluster analysis. Then, these groups were divided into separate homogenous subgroups with respect to genotype means. The cultivars in each subgroup have a similar grain yield response to the environments and, then, similar adaptation pattern, although the genotype groups differed in adaptation to these environments...